Betel Leaf Extract (Piper betle L.) Antihyperuricemia Effect Decreases Oxidative Stress by Reducing the Level of MDA and Increase Blood SOD Levels of Hyperuricemia Wistar Rats (Rattus norvegicus) - Sumarya, I M.; Adiputra, N.; Sukrama, I D. M.; Manuaba, Ida Bagus Putra (BALI MEDICAL JOURNAL, 2016)
Background: Betel leaf extracts (Piper betle L.) antioxidant activity and enzyme inhibitors of XO. Hyperuricemia cause oxidative stress by increasing the formation of reactive oxygen species (ROS) cause lipid peroxidation and oxygenation of low-density lipoprotein cholesterol (LDLc). Objective: The aim of this research was to determine the betel leaf extract as an anti hyperuricemia that can lower the blood uric acid levels and oxidative stress by lowering the levels of MDA and increase the SOD of hyperuricemia of the rat’s blood. Method: Experimental research was conducted with the design of The Randomized Post Test Only Control Group Design, on normal Wistar rats (Rattus norvegicus), administered with oxonic potassium (hyperuricemia) and the hyperuricemia rats either given betel leaf extract and allopurinol. After the experiment of uric acid levels, MDA and SOD in rat blood determined. Results: The results showed that the betel leaf extract significantly (p <0.05) lower uric acid levels, MDA and increase levels of SOD in rat blood. There is a positive correlation between the levels of uric acid with MDA levels and a negative correlation, although not significantly with SOD (p >0.05). Conclusion: It can be concluded that the betel leaf extract as an anti-hyperuricemia can lower the uric acid levels and decreases oxidative stress by lowering the levels of MDA and increasing the SOD.